Historical Origins of the Current Ukrainian Crisis - A. N. Artizov (Vestnik MGIMO-Universiteta)
Historical origins of the current Ukrainian crisis is a complex topic since it covers a thousand-year history and includes the main issues of the past and present of the people living on the East European Plain. The preparation of an anthology of archival documents in support of Vladimir Putin's well-known article «On the historical unity of Russians and Ukrainians» is being completed. Andrei Artizov, Head of the Federal Archival Agency, shares some of the results of the joint work of scientists and historians-archivists in this article.